If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = m + -1(-3) Multiply -1 * -3 -12 = m + 3 Reorder the terms: -12 = 3 + m Solving -12 = 3 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -12 + -1m = 3 + m + -1m Combine like terms: m + -1m = 0 -12 + -1m = 3 + 0 -12 + -1m = 3 Add '12' to each side of the equation. -12 + 12 + -1m = 3 + 12 Combine like terms: -12 + 12 = 0 0 + -1m = 3 + 12 -1m = 3 + 12 Combine like terms: 3 + 12 = 15 -1m = 15 Divide each side by '-1'. m = -15 Simplifying m = -15
| -12x^2-4x+3=0 | | 6=4x+4y | | y=ln(7x-3) | | 3(4x+7)=165 | | 6(c+1)=6+5c | | 3x-8-4x=-92 | | -99-2x=62-9x | | -2+21=m-6 | | 2(3-5x)=116 | | -9+3x+4x=-93 | | x-5=-4+8 | | 14+2x=(-30)-x | | X+(-19)=2 | | 43-2x=5x | | 2s+5=3s+8 | | -2(7x+10)=-20 | | b+45=120 | | 10x-4x(x-3)=6x+4 | | 8n+15-5n=19+n | | -7(7+2x)=-21 | | 9[x-2]=90 | | 14+2x=30-x | | 2(8-7x)=170 | | 13=8x-5-6x | | -16*11x=9x+18 | | w+36000=100000 | | 7y+4-5y=6+y-7 | | -2.3+t=5.9 | | 11=19-11 | | 5*[x-2]=7 | | 5s-2=4s+6 | | 12x^4-36x^3-24x^2=0 |